1990
DOI: 10.1002/elps.1150110115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of pregnancy‐associated plasma protein‐A by electrophoresis

Abstract: Gradient polyacrylamide gel electrophoresis, isoelectric focusing and multidimensional immunoelectrophoretic techniques have been applied in order to physico-chemically characterize pregnancy-associated plasma protein-A (PAPP-A). By lectin affinity immunoelectrophoresis, PAPP-A contained sialic acid, glucose/mannose and N-acetyl-alpha-D-galactosamine. Immunoelectrophoretic analyses after incubation with various glycolases confirmed these findings and demonstrated that PAPP-A contained glucuronic acid, perhaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Following its discovery, several biological roles of PAPP-A were proposed, including a function as a proteinase inhibitor, inspired by similarities with α-2-macroglobulin (α 2 M) and pregnancy zone protein (PZP) (Sinosich 1990). However, no consensus was established regarding its biological role or subunit organization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following its discovery, several biological roles of PAPP-A were proposed, including a function as a proteinase inhibitor, inspired by similarities with α-2-macroglobulin (α 2 M) and pregnancy zone protein (PZP) (Sinosich 1990). However, no consensus was established regarding its biological role or subunit organization.…”
mentioning
confidence: 99%
“…The first 25 years of PAPP-A -a useful protein of unknown function Human pregnancy-associated plasma protein-A (PAPP-A) was identified 40 years ago as a protein present abundantly in plasma of pregnant women (Lin et al 1974). Following its discovery, several biological roles of PAPP-A were proposed, including a function as a proteinase inhibitor, inspired by similarities with α-2-macroglobulin (α 2 M) and pregnancy zone protein (PZP) (Sinosich 1990). However, no consensus was established regarding its biological role or subunit organization.…”
mentioning
confidence: 99%
“…The concentration in serum reaches about 50 mg/liter at the end of pregnancy (2,3). PAPP-A was originally characterized as a high molecular weight homotetramer (1,4,5), but it has now been demonstrated that PAPP-A exists in pregnancy serum as a covalent, heterotetrameric 2:2 complex with the proform of eosinophil major basic protein (proMBP), PAPP-A/proMBP (6). The presence of proMBP in the circulation, as well as the existence of the PAPP-A/proMBP complex was revealed, in part, by the isolation of a PAPP-A and a proMBP peptide, linked together by a disulfide bond, from a digest of purified PAPP-A/proMBP (6).…”
mentioning
confidence: 99%
“…Although the PAPP-A mRNA can be found in many tissues, the placental production exceeds any other. The syncytiotrophoblast composes the PAPP-A subunit, while proMBP is synthesized in extravillous trophoblasts, and the two subunits are combined to create the final complex at the extracellular environment [3].…”
Section: Reviewmentioning
confidence: 99%